2018
DOI: 10.1038/s41467-018-04659-x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling law for excitons in 2D perovskite quantum wells

Abstract: Ruddlesden–Popper halide perovskites are 2D solution-processed quantum wells with a general formula A2A’n-1MnX3n+1, where optoelectronic properties can be tuned by varying the perovskite layer thickness (n-value), and have recently emerged as efficient semiconductors with technologically relevant stability. However, fundamental questions concerning the nature of optical resonances (excitons or free carriers) and the exciton reduced mass, and their scaling with quantum well thickness, which are critical for des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
918
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(1,002 citation statements)
references
References 56 publications
(86 reference statements)
61
918
5
1
Order By: Relevance
“…To thoroughly review such complicated relaxation, we first discuss the relationship between PL/TA and the density of excited states (both excitons and carriers). Specifically, the PL intensity is mainly derived from the radiative recombination of excitons rather than free carriers due to the large binding energy of both the 2D (hundreds of meV) and 3D (40 meV of CsPbBr 3 ) perovskite, leaving the PL rate proportional to the exciton density. In view of TA, both free carriers and excitons contribute to the bleaching signal, and the former presents a larger band filling effect due to its larger screening .…”
Section: Resultsmentioning
confidence: 99%
“…To thoroughly review such complicated relaxation, we first discuss the relationship between PL/TA and the density of excited states (both excitons and carriers). Specifically, the PL intensity is mainly derived from the radiative recombination of excitons rather than free carriers due to the large binding energy of both the 2D (hundreds of meV) and 3D (40 meV of CsPbBr 3 ) perovskite, leaving the PL rate proportional to the exciton density. In view of TA, both free carriers and excitons contribute to the bleaching signal, and the former presents a larger band filling effect due to its larger screening .…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the theoretically calculated E b values of CsPbCl 3 and CsPbBr 3 are greater than the thermal energy value at RT, which indicates that CsPbCl 3 and CsPbBr 3 are optically more favorable. In fact, the relative accuracy of theoretical calculations was confirmed by experimental temperature‐dependent absorption, optical absorption, and magnetoabsorption …”
Section: Crystal Structure and Optoelectronic Properties Of Perovskitmentioning
confidence: 78%
“…Compared to the 3D analogues,2 Dp erovskites have shown improved processability and stability towards water and light. [7][8][9] In this work, we describe how the incorporation of conjugated diynes into 2D lead halide perovskites and subsequent thermal treatment results in the topochemical formation of 2D lead halide perovskites that incorporate polydiacetylenes into their structure.F urthermore,w es how that by oxygen or iodine doping we can generate additional carriers that generate important changes in the properties of these materials, shifting the optical band gap from 3.0 to 1.4 eV and improving the conductivity by up to three orders of magnitude, effectively inverting the traditional quantum-well structure (Figure 1a,b). [1][2][3][4][5] Thei nsulating nature of the organic cations in 2D perovskites also disrupts the electronic structure of these materials,w hich leads to diminished light absorption (larger band gaps) and conductivities.T his peculiar electronic structure,w hich consists of alternating semiconducting and insulating layers,h as been described as aq uantum-well structure.…”
Section: Two-dimensional (2d) Organic-inorganic Hybrid Perovskitesmentioning
confidence: 99%
“…Compared to the 3D analogues,2 Dp erovskites have shown improved processability and stability towards water and light. [7][8][9] In this work, we describe how the incorporation of conjugated diynes into 2D lead halide perovskites and subsequent thermal treatment results in the topochemical formation of 2D lead halide perovskites that incorporate polydiacetylenes into their structure.F urthermore,w es how that by oxygen or iodine doping we can generate additional carriers that generate important changes in the properties of these materials, shifting the optical band gap from 3.0 to 1.4 eV and improving the conductivity by up to three orders of magnitude, effectively inverting the traditional quantum-well structure (Figure 1a,b).Seminal work by Tieke and collaborators [10][11][12][13] showed that irradiating 2D perovskites with unsaturated organic cations resulted in the topochemical polymerization of such cations with retention of the 2D hybrid perovskite structure.M ost studies by Tieke however,f ocused on the use of cadmium chloride layers and diene monomers,w hich have large band gaps and form polymers without notable electronic properties.L ater, Takeoka and co-workers incorporated polydiacetylenes in lead halide perovskites;however, they used gamma radiation to induce polymerization, which makes this technique unpractical for most applications. [1][2][3][4][5] Thei nsulating nature of the organic cations in 2D perovskites also disrupts the electronic structure of these materials,w hich leads to diminished light absorption (larger band gaps) and conductivities.T his peculiar electronic structure,w hich consists of alternating semiconducting and insulating layers,h as been described as aq uantum-well structure.…”
mentioning
confidence: 99%